DETERMINATION OF TOTAL BACTERIA COUNT AND SELECTION OF INJECTION WATER QUALITY RATING CHART FOR WATER FLOOD NEEDS IN SUMATRA OIL FIELDS - Nuraini Nuraini; Tjuwati Makmur (Testing Center for Oil and Gas LEMIGAS, 2007)
An important factor affecting the success of a water flood project for secondary recoveryis the quality of the water being injected. In this research, the water quality tests werefocused on determination of total bacteria counts of the analyzed injection water sampleusing ASTM D 5465-93 and selections of injection water quality rating chart for waterflood needs in Sumatra oil fields. The results of microbiological laboratory tests of allanalyzed injection water samples showed three parts. An injection water sample of N - 82containing type of bacteria Bacillus sp with the total bacteria counts 5.02 x 100 colonies/ccwas categorized as no. 1 water quality rating chart. Subsequently, G – GS injection watersample indicated Bacillus sp with total bacteria counts 4.28 x 101 colonies/cc and BacillusLaterosporous with total bacteria count 3.31 x 101 colonies/cc for G – 90 water sample.Two samples mentioned above were classified as no. 2 water quality rating chart. Next,Bacillus Alvei was found in T – 21 injection water sample with total bacteria count 1.85 x102 colonies/cc and Bacillus Pathothenticus in T – GS injection water samples with totalbacteria count 2.61 x 102 colonies/cc. Position of water quality rating chart for both lastsamples were no. 3. These results gave valuable and useful information before implementationof water flood in the oilfield.